Development of the Android Application for the Landslide Disaster Mitigation Real-time System based on Firebase Server and OneSignal - Aif Umar Nawawi; Arjuni Budi Pantjawati; Aip Saripudin; Nurul Fahmi Arief Hakim; Nurhidayatulloh Nurhidayatulloh; Novia Karostiani; Bagaskara Anandayutya; Alvin Dzaki Pratama Darmawan (National Research and Innovation Agency, 2024)
This article presents the development of SIDASIBELO (Landslide Information and Mitigation System), an Android-based application for real-time landslide monitoring and early warning. This system integrates data from several sensors that measure soil moisture, rainfall, slope angle, and ground vibrations at the monitored locations. The Firebase Real-time Database stores and transmits sensor data, while Firebase Cloud Messaging and OneSignal enable push notifications to alert users about potential landslide risks. There are four output status levels: SAFE, ALERT, CAUTION, and WARNING, which are determined based on a comprehensive analysis of the monitored parameters. Mitigation strategies include real-time parameter monitoring, early warnings, evacuation guidance, and user education on landslide preparedness. Testing on several Android devices demonstrated high compatibility, with an average successful server connection rate of 92.86%. Latency tests indicated an average response time of 894 ms from the input device to the database, 1.29 ms from the database to the Android device, and 2725 ms for push notifications. The system's total daily bandwidth usage for real-time data transmission is 27,648 MB, indicating high efficiency without overburdening the server's performance. While the app operates efficiently under ideal conditions, unstable network connections can lead to data retrieval failures or, in worst cases, app malfunctions. This remains a key challenge for our system. This system aims to raise awareness of landslide risks and enable timely evacuation, which could potentially reduce the negative impacts of landslides in vulnerable areas.